FOR USE FOAM FILLING IRON REMOVAL WATER - , В. О., М. М. (Municipal economy of cities. Series: «Economy science», 2013)
Definitely promising uses of plastics in water management. Results of Hydraulic Research filtering process due to foam filling, results filtering and cleaning processes.